Spatio - temporal data and geovisualization:Powerpoint - Kraak, M.J. (University of Twente, 2020)
This lecture presents: Snow in the north east of the USA; Snow dynamics; Final snow count; New York Times mapping; Traffic intensity; Perception problems with change; Multiple coordinated views.